Gender in Solomon's Song Of Songs : discourse analytical abduction to a gynocentric hypothesis - Haines, Alastair Ian (Eugene : Wipf & Stock Publishers, 2016)
The thesis shows that the Song of Songs can be read as a circular sequence of sub-poems, that follow logically from one another if they are understood as contributing to two main points, made in a woman's voice. The woman urges men to take romantic initiative to be committed exclusively and for life, and urges women three times to wait until they are approached by such men. If this reading is the best explanation of the text of the Song, then the Song is a unified work centered on a woman singing about human romantic love from a woman's perspective.
Pages:1 to 25; Pages:26 to 50; Pages:51 to 75; Pages:76 to 100; Pages:101 to 125; Pages:126 to 150; Pages:151 to 175; Pages:176 to 200; Pages:201 to 225; Pages:226 to 250; Pages:251 to 275; Pages:276 to 300; Pages:301 to 310
Online resource; title from PDF title page (EBSCO, viewed February 23, 2017)
Includes bibliographical references.
Master record variable field(s) change: 072, 082
Keywords: Bible. -- Criticism, interpretation, etc; Gender identity in the Bible; Sex in the Bible; RELIGION / Biblical Studies / Old Testament; RELIGION / Biblical Studies / Wisdom Literature; Electronic books